From aspectual to degree quantifiers: Context expansion of por completo and completamente in Spanish and Portuguese - Katharina Gerhalter; Stefan Koch (ELAD-SILDA)
This paper examines four adverbial cognates in Spanish and Portuguese, Sp. por completo, Pt. por completo, Sp. completamente, and Pt. completamente, from a historical and functional point of view. Our analysis is based on three major corpora of Spanish and Portuguese (CDH, CdP, and CORPES XXI). The four adverb(ial)s share the same base adjective or etymon, Lat. completus, from which Pt. por completo only stems indirectly, as it is probably a calque from Sp. por completo. These four cognates are polyfunctional: they are aspectual quantifiers and degree quantifiers. We find that the interpretation of these adverbials primarily depends on the semantics of the modified element as well as on the broader context of the sentence. The syntactic position of the adverbials plays a minor role in this interpretation. We argue that the degree quantifier function develops from the aspectual function and that this is the result of a diachronic evolution via ambiguous bridging/critical contexts and switch/isolate contexts. This evolution started in the 15th century with Sp. completamente, and we consider this a case of context expansion (encompassing host-class expansion, semantic-pragmatic context expansion, and syntactic expansion). Sp./Pt. por completo and completamente, as degree quantifiers, retain semantic traits from their original aspectual meaning and remain restricted to certain contexts: they only modify linguistic elements whose semantics has the property of a maximum limit. Therefore, they are not conventionalized as degree quantifiers. Regarding syntax, we observe a difference between Sp./Pt. por completo and Sp./Pt. completamente: the latter is attested right away as a pre-posed adjective-modifier, whereas the former develops this pattern step-by-step (first, post-position, and only later on pre-position).